The ENSO-induced South Pacific Meridional Mode - Dewitte, Boris; Concha, Emilio; Saavedra, Diego; Pizarro, Oscar; Martinez-Villalobos, Cristian; Gushchina, Daria; Ramos, Marcel; Montecinos, Aldo (Frontiers in Climate, 2023)
Previous studies have investigated the role of the Pacific meridional mode (PMM), a climate mode of the mid-latitudes in the Northern and Southern Hemisphere, in favoring the development of the El Niño Southern Oscillation (ENSO). However little is known on how ENSO can influence the development of the PMM. Here we investigate the relationship between ENSO and the South Pacific Meridional Mode (SPMM) focusing on strong SPMM events that follows strong El Niño events. This type of events represents more than 60% of such events in the observational record and the historical simulations of the CESM Large ensemble (CESM-LE). It is first shown that such a relationship is rather stationary in both observations and the CESM-LE. Our analyses further reveal that strong SPMM events are associated with a coastal warming off northern central Chile peaking in Austral winter resulting from the propagation of waves forced at the equator during the development of El Niño events. The time delay between the ENSO peak (Boreal winter) and this coastal warming (Austral winter) can be understood in terms of the differential contribution of the equatorially-forced propagating baroclinic waves to the warming along the coast. In particular, the difference in phase speeds of the waves (the high-order mode the wave the slower) implies that they do not overlap along their propagation south of 20°S. This contributes to the persistence of warm coastal SST anomalies off Central Chile until the Austral summer following the concurrent El Niño event. This coastal warming is favorable to the development of strong SPMM events as the South Pacific Oscillation become active during that season. The analysis of the simulations of the Coupled Intercomparison Project phases 5 and 6 (CMIP5/6) indicate that very few models realistically simulate this ENSO/SPMM relationship and associated oceanic teleconnection.